Nursing Students' Experiences of Learning Evidence-Based Practice Through a Flipped Classroom: A Qualitative Study. - Pérez-Muñoz, Verónica; Ramos-Morcillo, Antonio Jesús; Molina-Rodríguez, Alonso; Ruzafa-Martínez, María (Nursing Reports, 2026)
Background: Evidence-based practice (EBP) is a cornerstone of high-quality and safe nursing care. However, undergraduate nursing students often experience cognitive, methodological, and contextual barriers to learning and applying EBP. Active teaching strategies, such as the flipped classroom, may support the development of EBP competencies, yet qualitative evidence exploring students' learning experiences remains limited. Objectives: To explore nursing students' perceptions and experiences of learning evidence-based practice through a flipped classroom model. Methods: A qualitative descriptive study was conducted at the Faculty of Nursing of the University of Murcia (Spain). Purposeful maximum variation sampling was used to recruit undergraduate nursing students from the second and fourth academic years who had completed an EBP course delivered using a flipped classroom approach supported by an online learning platform. Twenty semi-structured interviews were conducted via videoconference. Data were transcribed verbatim and analyzed using reflexive thematic analysis with independent coding by two researchers and consensus procedures. Ethical approval and confidentiality were ensured. Results: Three main themes were identified: (1) transformation of the meaning of EBP learning and professional role, (2) cognitive and metacognitive processes in EBP learning, and (3) the learning experience as a catalyst for deep learning. Students described a shift from initial fear and perceived difficulty toward recognizing the practical value of EBP, accompanied by increased critical thinking, autonomous learning, and a growing evidence-informed professional identity. The flipped classroom model facilitated engagement and understanding, while the transfer of learning to clinical practice was influenced by contextual facilitators and barriers. Conclusions: Learning EBP through a flipped classroom was experienced as a transformative process that fostered critical thinking, self-regulated learning, and the construction of an evidence-oriented professional identity among nursing students. Strengthening information literacy skills and improving alignment between academic and clinical environments may enhance the sustainable application of EBP in clinical practice.